The testimonal rhetoric in narratives from Trip, TPM and Rolling Stone - Leal, Bruno Souza; Lage, Igor (Brazilian journalism research, 2015)
This article analyzes stories from the magazines Trip, TPM and Rolling Stone in order to reflect about the testimonial dimension of first-person journalistic narratives. Recovering studies on the testimony in History, especially those related to the survivors of World War II, and also in Social Communication, the article ponders that, in general, the first-person narrative does not always constitute journalistic experiences by the same ways. Thus, it is observed the setting of a “testimonial rhetoric” on different forms, i.e., the search for a co-presence effect, essential for the authentication of the reports, the narrator and the presented events.